Paleo-Environmental Variation and Its Control on the Organic Matter Accumulation in Black Shale of the Permian Gufeng Formation in the Lower Yangtze Area, South China - Shen, Weibing; Wang, Yangyang; Zheng, Ziyu; Shen, Shihao; Xie, Hongzhe; Qin, Haoyi; Bai, Maquzong (Frontiers in Earth Science, 2022)
Mechanism of the organic matter (OM) accumulation in the Middle Permian Gufeng Formation shale in South China is lack of constraints, which restricts the source rock evaluations and shale gas explorations. To decipher the OM accumulation of the Gufeng Formation, geological and geochemical results related to paleo-environmental variations are presented from the shelf Putaoling section in South China. The OM accumulation in the Gufeng Formation is vertically heterogeneous, shown by a medium total organic carbon (TOC) content (2.3%) in the lower member and a high TOC content (9.6%) in the upper member. The organic-rich shales of the Gufeng Formation are deposited in a complex paleo-environment with restrained water conditions, a warm and humid paleoclimate, a relatively strong chemical weathering, significant hydrothermal activities, a high primary productivity, fluctuating redox conditions, and a relatively high sedimentary rate. Compared to the lower member deposited under anoxic conditions, the upper member is formed in a dominantly euxinic environment with higher productivities. The seawater deoxygenation and the upward-increasing productivity jointly lead to the vertical heterogeneity of the OM accumulation in the Gufeng Formation. Thus, an ‘integrated model’ for the OM accumulation in the Gufeng Formation is established, and which adds to our knowledge that no a single factor or model can explain the OM accumulation in all sedimentary environments.